Impact of drying methods and storage conditions on the reactivation of Sporosarcina pasteurii for microbial induced carbonate precipitation - Hanisch, Patrick; Pechtl, Markus; Eulenkamp, Constanze; Krickl, Sebastian; Melchin, Timo; Huber, Robert (Frontiers in Materials, 2025)
The drying of bacteria using various methods is a widely used technique for long-term stabilization across different applications. For organisms capable of producing the enzyme urease, which are used in microbial induced carbonate precipitation (MICP), drying may also offer promising new fields for application. In the present study, two drying methods, fluidized bed drying and freeze-drying, were applied to Sporosarcina pasteurii, both with and without the commonly used cryoprotectant maltodextrin. The dried samples were evaluated in terms of cell viability, storage stability (based on urease activity) at three different temperatures (room temperature, 4 °C and −20 °C), and their subsequent performance after 92 days of storage for a typical MICP application, aiming to increase the uniaxial compressive strength of quartz sand columns. Maltodextrin positively affected cell viability and urease enzyme stability, with the freeze-dried powder showing the highest cell viability at 21%, while fluidized bed drying resulted in less than 1% viability. Storage temperature influenced urease stability, with a decrease in enzyme activity at −20 °C being 22.63%, and showed a further decrease at higher temperatures, with 67.86% at room temperature and 64.23% at 4 °C, respectively for the freeze-dried powders. Nevertheless, both powders from the two drying methods improved the compressive strength of sand columns via MICP, with UCS values reaching up to 10.81 Nmm2 for the freeze-dried powders. The findings demonstrate that both fluidized bed and freeze-drying techniques allow Sporosarcina pasteurii to be stored at room temperature without the need for a protective agent, highlighting their practicality for MICP applications and demonstrating their potential for large-scale use in civil engineering and geoengineering.